(untitled) (Texas Journal of Philology, Culture and History, 2023)
This article discusses the stages of development of the phraseology of the Uzbek language, and also presents a small analysis of the phraseological units of the Uzbek language. This is the soul of any national language, in which the spirit and originality of the nation is expressed in a unique way. Phraseology, being part of the language picture of the world, reflects the national mentality of a native speaker